GUSTAVO OTT'S DRAMATIC COCKTAILS. - Mujica, Barbara (Americas)
Features Venezuelan playwright Gustavo Ott and his scripts. Educational background of the playwright; Subjects of his scripts; Efforts of the playwright to try various writing styles.